2012
DOI: 10.1093/ndt/gfs407
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and cardiovascular events in online haemodiafiltration (OL-HDF) compared with high-flux dialysis: results from the Turkish OL-HDF Study

Abstract: The composite of all-cause mortality and nonfatal cardiovascular event rate was not different in the OL-HDF and in the high-flux HD groups. In a post hoc analysis, OL-HDF treatment with substitution volumes over 17.4 L was associated with better cardiovascular and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
383
8
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 427 publications
(457 citation statements)
references
References 28 publications
18
383
8
13
Order By: Relevance
“…Post hoc analyses of three large randomized controlled trials-CONTRAST (16), the Turkish HDF Study (29), and ESHOL (Estudio de Supervivencia de Hemodiafiltración On-Line) (30)-comparing HDF to HD in terms of mortality and cardiovascular events found a relation between high convection volumes and lower mortality risk. We did not find that high convection volumes were related to rate of change of LVM, EF, and PWV.…”
Section: Convection Volumementioning
confidence: 99%
“…Post hoc analyses of three large randomized controlled trials-CONTRAST (16), the Turkish HDF Study (29), and ESHOL (Estudio de Supervivencia de Hemodiafiltración On-Line) (30)-comparing HDF to HD in terms of mortality and cardiovascular events found a relation between high convection volumes and lower mortality risk. We did not find that high convection volumes were related to rate of change of LVM, EF, and PWV.…”
Section: Convection Volumementioning
confidence: 99%
“…In the case of ESHOL, this was both in the 23.1-25.5 L/treatment cohort and in the >25.4 L/treatment cohort [7] . In CON-TRAST, benefit was seen in the >21.95 L/treatment cohort [8] and in the Turkish study >19.5 L/treatment [9] . The true benefit delivered by HDF remains unclear as caution must be taken when interpreting data from such analysis.…”
Section: Clinical Outcomes In Hd: What Progress Have We Made?mentioning
confidence: 86%
“…Whether HDF reduces mortality is currently a matter of debate. The CONTRAST [15] and the Turkish online hemodiafiltration study [16] have both shown no difference in mortality between HD and online HDF in adult patients. However, patients, who received a convective volume of >15 l (CONTRAST) or 17.4 l (Turkish online hemodiafiltration study), had a significantly lower mortality rate.…”
Section: Introductionmentioning
confidence: 94%